The Ethical Aspects of Applying Artificial Intelligence in the Healthcare System - Yuliana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Artificial intelligence is abundant nowadays, including healthcare practice. However, there are ethical aspects of applying artificial intelligence (AI) in healthcare practice. The paper aims to describe the ethical aspects of applying artificial intelligence (AI) in the healthcare system. This paper is a narrative literature review. Literature was taken from Science Direct, PubMed, and Google Scholar. Selected journals were published within 5 years. AI-based algorithms commonly work based on the provided data. Nevertheless, the variations among patients’ conditions, insurance records, and diagnostic results are wide. Some data such as social determinants might not be seen by the AI system. This kind of data determines the biases in data sets and health disparities. Therefore, the algorithms should be well designed to minimize bias and align with the ethical dimensions. Predictive algorithms might be used to predict care decisions and outcomes. Incorrect diagnosis might be developed while using AI tools directly without expert opinion. In conclusion, the ethical dimensions of applying AI in the healthcare practice are minimizing bias, determining the variations of social conditions among patients, and using expert opinion other than relying on AI only.